Three-Dimensional Silicon-Germanium Nanostructures for CMOS Compatible Light Emitters and Optical Interconnects. (13th May 2008) - Tsybeskov, L.; Lee, E.-K.; Chang, H.-Y.; Kamenev, B. V.; Lockwood, D. J.; Baribeau, J.-M.; Kamins, T. I.
Abstract : Three-dimensional SiGe nanostructures grown on Si (SiGe/Si) using molecular beam epitaxy or low-pressure chemical vapor deposition exhibit photoluminescence and electroluminescence in the important spectral range of 1.3–1.6 μ m. At a high level of photoexcitation or carrier injection, thermal quenching of the luminescence intensity is suppressed and the previously confirmed type-II energy band alignment at Si/SiGe cluster heterointerfaces no longer controls radiative carrier recombination. Instead, a recently proposed dynamic type-I energy band alignment is found to be responsible for the strong decrease in carrier radiative lifetime and further increase in the luminescence quantum efficiency.